Результати імплантації трифокальних інтраокулярних лінз при факоемульсифікації катаракти на очах з міопією високого ступеня - Завгородня, Наталія Григорівна; Михайленко, Надія Вікторівна; Zavgorodnia, N.; Mykhailenko, N. (Одеса: Чорномор’я, 2019)
Висока міопія є ускладнюючим фактором при хірургічному лікуванні катаракти, що впливає на досягнення високих зорових результатів. Тривалий час в науковій літературі велась дискусія про доцільність імплантації мультифокальних інтраокулярних лінз та про оптимальний вибір формули розрахунку штучного кришталика. Поява на ринку України трифокальних інтраокулярних лінз знову підняла питання про доцільність їх використання при катаракті на очах з високою міопією. Cataract surgery is associated with such a complicating factor as high myopia. Infrequent complications of the ocular fundus, which are not always possible to detect in the preoperative period, it is hard to predict high postoperative visual acuity. We analyzed the results of phacoemulsification of cataracts with the implantation of the trifocal intraocular lens LISAtri (Сarl Zeiss) and the monofocal IOL of ASFINA (Сarl Zeiss) in the eyes with high myopia and marked a significant increase in visual acuity in both groups. After surgery none of the patients had to use distance spectacles, however, the patients who received a monofocal intraocular lens had to use reading spectacles, in the meantime, the patients who received a trifocal intraocular lens achieved better distance visual acuity, at moderate and close distances, which resulted in significant improvement of quality of life and better adaptability to new visual conditions.
Visual outcomes of trifocal intraocular lens implantation during cataract phacoemulsification in highly myopic eyes
Keywords: матеріали конференцій; трифокальні інтраокулярні лінзи; імплантація; факоемульсифікація катаракти; міопія високого ступеня; trifocal intraocular lens; implantation; cataract phacoemulsification; highly myopic eyes